2018
DOI: 10.1111/mcn.12639
|View full text |Cite
|
Sign up to set email alerts
|

Development of a dietary screening questionnaire to predict excessive weight gain in pregnancy

Abstract: Excessive gestational weight gain (GWG) is a risk factor for several adverse pregnancy outcomes, including macrosomia. Diet is one of the few modifiable risk factors identified. However, most dietary assessment methods are impractical for use in maternal care. This study evaluated whether a short dietary screening questionnaire could be used as a predictor of excessive GWG in a cohort of Icelandic women. The dietary data were collected in gestational weeks 11-14, using a 40-item food frequency screening questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…Insufficient iodine status was observed for the first time in an Icelandic population, most likely related to a decline in fish and dairy intake. The reasons for the decrease in fish and dairy intake in Iceland (11,12,16) remain unknown. However, it could be speculated that public discussion on suggested negative health effects of dairy consumption and increased awareness of environmental aspects might have contributed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insufficient iodine status was observed for the first time in an Icelandic population, most likely related to a decline in fish and dairy intake. The reasons for the decrease in fish and dairy intake in Iceland (11,12,16) remain unknown. However, it could be speculated that public discussion on suggested negative health effects of dairy consumption and increased awareness of environmental aspects might have contributed.…”
Section: Resultsmentioning
confidence: 99%
“…Women selected between 10 potential frequency responses ranging from 'less than once a month' to 'more than 5 times a day'. The development of the FFQ has previously been described in detail and the FFQ published (12). The frequency responses for fish (lean and oily) and dairy intake (drinking milk and fermented dairy products, excluding cheese) were used to categorize women to compare UIC and I/Cr ratio across intake groups.…”
Section: Dietary Intake and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1113 women from the GraviD cohort were eligible for inclusion in this paper. Power calculations showed that this sample size would yield 77% power (alpha 0.05) to detect a 23% increased risk of excessive GWG among those with poor diet [23], (31% vs. 38% excessive GWG among those with high and poor quality diet, respectively). We assumed an overall 60% prevalence of poor dietary quality [16].…”
Section: Discussionmentioning
confidence: 99%
“…The PREWICE cohort (PREgnant Women of ICEland) has been described elsewhere [18]. All women ( n = 2734) with singleton pregnancies who attended a routine early ultrasound (11–14 week of gestation) at the prenatal diagnostic unit at Landspitali University Hospital in Reykjavik, South Iceland between 1 October, 2015 to 31 September, 2016, were invited to take part in the study.…”
Section: Methodsmentioning
confidence: 99%